Succeeding and persevering at teaching: how Self-determination Theory can shape our understanding of motivation for first-year teachers - Alberto, Jamie Philip (My University, 2024)
The teaching profession in the U.S. is currently experiencing a years-long deficit between the number of new teachers required to fulfill the needs of today’s PK-12 public school job openings and the number of people choosing to enter the profession (National Center for Education Statistics, 2023). The problem is further exacerbated when paired with the knowledge that, over the last decade, an average 8% of existing teachers has chosen to exit the profession each year (National Center for Education Statistics, 2023). Using self-determination theory (SDT) as a theoretical framework, this study sought to investigate first-year teacher motivation, a key component of self-determination, with the hope of later applying the knowledge learned to help bolster new teacher success and perseverance. Using qualitative secondary analysis (QSA), this research (the current study) built upon, and looked to add to the findings of, earlier research (the initial study). The data set for the initial study was comprised of transcripts from a longitudinal case study conducted by researchers from the Kansas State University-College of Education (KSU-COE), aimed at satisfying requirements for the Council for the Accreditation of Educator Preparation’s (CAEP) Standard 4: Capturing Completer Impact on PK-12 Students (Kansas State University-College of Education, 2022). The current study made use of transcripts spanning three school years (the 2019/2020 school year through the 2021/2022 school year) and included answers to interview questions from 56 participants, all first-year/new teachers in K-12 public education. Employing QSA methodology, new research questions centered on first-year teacher self-determination and motivation were applied to the transcript data from 17 focus group interviews. Open coding, for the primary research question, brought forward 233 unique codes related to first-year teachers’ motivation through the promotion or thwarting of self-determination. From the unique codes, eight salient themes were drawn (4 for promoting self-determination and 4 for thwarting self-determination) and discussed for their importance to teacher success and perseverance. Content analysis, for three subsidiary research questions, was used to unveil ways in which first-year teachers embody motivation through displays of the three components of SDT, which are competence, autonomy, and relatedness. The emergent themes and content analysis findings are discussed for broader application to improving the success and perseverance, and ultimately retention, of new teachers.
Keywords: Self-determination Theory; First-year teachers; College of Education; Motivation